ANALYSIS OF DISTRIBUTION PATTERN OF FUEL WOOD AND CHARCOAL IN ZARIA LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Samira Bello; Kibbon, Adamu Usman; Akpu, Akpu Benedine (FUDMA JOURNAL OF SCIENCES, 2021)
Energy use is an essential requirement for socioeconomic development of any society. This research aimed at analyzing fuel wood and charcoal distribution pattern in Zaria Local Government Area Kaduna State Nigeria. The aim was achieved through the following objectives which are to: identify the distribution of fuel wood depots in the study area; analyse the distribution pattern of fuel wood in the study area and examine the seasonality, time and mode of fuel wood distribution in the study area. This research used both quantitative and qualitative method in data analysis. Findings from the research revealed two types of fuel wood vendor depots exists in the study area which are classified as either major or minor  types which shows that fuel wood vendor depots are mostly concentrated around the residential areas especially within the built-up land, also, charcoal is mostly sourced around Kachia and Lokoja Abuja Express way. Results from in-depth interview with the fuel wood vendors indicates that there are two types of fuel wood vendors: the mobile and the stationary vendors. It has been recommended in this study that the Government should come up with a policy guidelines to regulate and sanitise the number of minor fuel wood depots in the study area for a cleaner, safer and regulated environment. The relevant authorities should promulgate penalties for violators of the policy guidelines in order to ensure that the environment is kept safe from soil degradation as a result of the activities of the fuel wood depots and environmental pollution.
Keywords: Distribution, Pattern, Fuel Wood, Charcoal, Zaria.